KINERJA RANTAI PASOK BUNGA POTONG DI KOTA DENPASAR - dice fice siska; Ketut Budi Susrusa; I Made Sudarma (Universitas Udayana, 2019)
Activities related to international and national meetings in Bali require cut flowers and their arrangements as a means of decoration and so on. Bali only produces a few types of cut flowers so it is supplied by cut flowers from outside Bali. This study aims to analyze the performance of cut flower supply chains in Denpasar City. The study was conducted in Denpasar with a descriptive qualitative approach. Determination of respondents using the snowball method with a total of 53 people consisting of farmers, suppliers, distributors, retailers and cut flower consumers. The results showed that the four types of cut flowers that dominated the cut flower market in Denpasar were roses, chrysanthemums, peacock and savory night. There were four large distributors who distribute cut flowers to 76 retailers in Denpasar City. Cut flowers from regions in West Java and East Java are sent every day. When payment can be made in cash which is directly paid on the spot, with credit or by transfer using mobile banking. Supply chain performance can be seen from the farmer's share ranges from 30% - 45% of the retailer's price. Which has the lowest share of farmer’s share was nightly flowers (30%) followed by roses (35%) then pikok flowers (36%) and the highest was chrysanthemums (45%). Share prices at the supplier level ranges from 40% - 65% of the retail price and at the distributor level ranges from 50% - 80% of the retail price. Revenue and cost ratios are dominated by retailers with a range between 4.71 - 10.76. Each member of the marketing agency performs different marketing functions depending on the needs including: product transportation, sorting and grading, packaging, packaing, transportation and distribution. Herewith the costs incurred have an impact on the prices received by end consumers. The concentration ratio (CR 4) at the retail level is 42.17 or belongs to a weak oligopoly market structure. Keywords: Cut flowers, supply chain performance